The Effect of Omega-3 Fatty Acid Supplementation on Language and Personal-Social Development of Stunted Toddlers in the Bakunase Public Health Center Area - Liswaty Ga, Jefty; Adu, Apris A.; Jutomo, Lewi; Roga, Andreas Umbu; Berek, Noorce Christiani (Eduvest - Journal of Universal Studies, 2025)
This quasi-experimental study with a non-equivalent control group aimed to analyze the effects of omega-3 supplementation on early childhood development, focusing on gross motor skills, fine motor skills, language development, and social skills among stunted children aged 1–3 years in the Bakunase Health Center area. Malnutrition remains a serious issue in Indonesia, with 20.6% underweight, 18.4% stunted, and 9.4% wasting toddlers reported in Kupang City in 2024. A total of 20 participants were divided into treatment and control groups (10 each), and data were collected using questionnaires and analyzed with the Wilcoxon Signed Rank and Mann-Whitney tests. Results showed that omega-3 supplementation significantly improved language (p = 0.034) and social skills (p = 0.046) in the treatment group, with no significant changes observed in gross (p = 1.000) or fine motor skills (p = 0.317). No improvements were found in any domain in the control group, while the Mann-Whitney test confirmed significant differences between the two groups in language and social development (both p = 0.012).